Chemical Composition and Locomotors Activity of Essential Oils from the Rhizome, Stem, and Leaf of Alpinia malaccencis (Burm F.) of Indonesian Spices - Muchtaridi Muchtaridi, Ida Musfiroh, Anas Subarnas, Ikhsan Rambia, Hokcu Suganda, M. Enas Nasrudin (Journal of Applied Pharmaceutical Science, 2014)
The essential oils of three parts of the plant Alpinia malaccencis (Burm f.) (Zingiberaceae) collected from Sumedang, West Java Province has been studied. Determination of essential oil components from the rhizome, stem, and leaf of Alpinia malaccencis (Burm f.) was performed by confirmation of the linear retention index (LRI) and comparing the NIST library peak with data reported in the literature, the mass spectrum peaks with literature data. The essential oils obtained from rhizome, stem, and leaf of Alpinia malaccencis (Burm f.) by steam distillation was 1.22%, 0.25%, and 0.7%, (w/w), respectively. Rhizome oil composition was almost similar with stem oil with methyl cinnamate as the major component. Composition of leaf oil is different from rhizome and stem oil which dominated α-pinene (30.57%). The rhizome in doses 0.1 ml (47.09 %) had stronger locomotor inhibition activity compare than stem (26.97 %) and leaf oils (32.23 %) in doses 0.1 mL.
Keywords: Alpinia malaccencis (Burm f.), methyl cinnamate, LRI, and &alpha; -pinene, 1.8-cineole.